2030 conservation targets for European terrestrial mammals using the favourable conservation status concept - Alessandra D’Alessio; Marco Davoli; Carlo Rondinini; Michela Pacifici (Scientific Data)
Abstract The European Habitats Directive lists species and habitats of conservation priority for member states of the European Union, and prescribes that they achieve a favourable conservation status. The benchmark for assessing whether species achieve this status is provided by favourable reference values of distribution and population size. These values cannot be used directly as conservation targets, because they are incomplete, incomparable as they are identified through different methods, and not necessarily achievable in a specified time frame. We set conservation targets for the year 2030 for 81 European terrestrial mammals listed in Annexes II and IV of the Habitats Directive, and/or threatened at European level according to the IUCN Red List of Threatened Species, based on the concept of favourable onservation statuts. We used several methods, including models of population growth and range expansion to 2030, and a reference-based approach. These targets can be used to plan conservation actions for priority mammals, such as increasing protected area coverage to 30% of Europe as envisaged in the European Biodiversity Strategy 2030.